Effect of genotypes on soyabean seed quality development under West African Rainfed conditions - M. A., Adebisi; D. K., Ojo (Universiti Putra Malaysia Press, 2001)
Effect of genotypes on soyabean seed quality development was monitored under rainfed conditions at Abeokuta between July and November, 1997. A consistent increase in rate of normal germination and seedling emergence occurred among early harvests. Greatest germination rate was detected in seeds harvested around physiological (functional) and harvest (full) maturity stages. Seedling emergence was significantly influenced by seed harvest date in all soyabean entries. Germination and emergence increased as soyaben seed development progressed and was greatest for seeds harvested between R7 and R8 in all soyabean cultivars. Enforced desiccation to 10% moisture content promoted germination of seeds harvested around physiological maturity stages. The onset of desiccation tolerance fell between physiological and harvest maturity stages in all the six soyabean cultivars. The rapid decline in seedling emergence of artifically dried seeds at 50d after mtff as against 60d after mtff for normal laboratory gemination indicated that seedlots of initial good germination may not necessarily produce high seedling emergence under good seeding condition due to differences in genotypes. Association of seed characters such as seed size, seed weight, germinability and emergence ability is essential in soyabean breeding to facilitate selection of genotypes with good seed quality, thereby reducing elaborate storage and screening methods.